Patayin sa sindak si Barbara (Quezon City ABS-CBN, 2005)
A woman's simple wish to earn filial love and acceptance results to a terrifying turn of dark events. Barbara (Kris Aquino) surrenders her man, Fritz (Albert Martinez) to the arms of her neurotic half-sister Ruth (Jodi Sta. Maria) in order to win her affection and that of her mother's Amanda (Susan Roces). Since Fritz could love no other than Barbara, his marriage with Ruth becomes a spectacle of Ruth's raving jealous Fritz, Ultimately heading to her suicide. Ruth's spirit, however, resists resting in peace, and her obsession crosses over to the afterlife - Ruth haunts the entire family and uses her own child Karen (Celine Lim) as an instrument to carry out her ominous revenge.
DVD
Based on the film Patayin sa Sindak si Barbara in 1974
Executive producer, Malou N. Santos ; directed by Jerry Lopez Sineneng, Gilbert G. Perez.
Susan Roces, Kris Aquino, Albert Martinez, Jodi Sta. Maria.
Keywords: Horror--Feature.; Television serials